2012
DOI: 10.1021/am3000825
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensionally Macroporous Fe/C Nanocomposites As Highly Selective Oil-Absorption Materials

Abstract: In this study, three-dimensionally macroporous Fe/C nanocomposites were investigated as highly selective absorption materials for removing oils from water surface. The macroporous nanocomposites were synthesized by sintering a mixture of closely packed polystyrene microspheres and ferric nitrate precursor. These nanocomposites exhibited superhydrophobic and superoleophilic properties without the modification of low-surface-energy chemicals. And the pore size of the nanocomposites, which is crucial for the oil-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(134 citation statements)
references
References 36 publications
4
130
0
Order By: Relevance
“…In this way, 3D-SPMAs could be easily guided towards the polluted region so as to adsorb floating oil spills. Actually, almost all works about hydrophobic 3D-SPMAs have demonstrated this feature, [4,33,[39][40][41]92,97,106,112] such as CNTs sponges, MWNTs/PDMS nanocomposites, and polyurethane/iron oxide foams (Figure 13a-c). However, it should be noted this magnetic-driven adsorption process only accounts for the treatment of on-water oil spills.…”
Section: Advantages Of 3d-spmas In Oil Uptakementioning
confidence: 94%
See 2 more Smart Citations
“…In this way, 3D-SPMAs could be easily guided towards the polluted region so as to adsorb floating oil spills. Actually, almost all works about hydrophobic 3D-SPMAs have demonstrated this feature, [4,33,[39][40][41]92,97,106,112] such as CNTs sponges, MWNTs/PDMS nanocomposites, and polyurethane/iron oxide foams (Figure 13a-c). However, it should be noted this magnetic-driven adsorption process only accounts for the treatment of on-water oil spills.…”
Section: Advantages Of 3d-spmas In Oil Uptakementioning
confidence: 94%
“…[35,38,41,58,59,[91][92][93] For example, Brown et al prepared low-density Fe 2 ZnO 4 aerogels (≈12-15 mg cm -3 ) by epoxide-induced co-precipitation of ferric nitrate and zinc nitrate followed by supercritical drying. [58] For some metal salts with low solubility, templating can be an alternative choice.…”
Section: Dry 3d-spmas Based On Magnetic Building Blocksmentioning
confidence: 99%
See 1 more Smart Citation
“…8a, the magnetic superhydrophobic CF aerogels exhibited absorption capacities ranging from 29 to 70 times their weight for above oils and organic solvents. The sorption capacities are superior to many previously reported sorbents [17,[27][28][29], such as PDMS sponges (4.7-20 times) [17], graphene/a-FeOOH composites (10-30 times) [27], 3D macroporous Fe/C (4-10 times) [29]. Furthermore, repeated recycle tests were performed for its essential in oil/chemical cleanup.…”
Section: Resultsmentioning
confidence: 82%
“…For examples, Pan et al investigated a magnetic macroporous Fe/C nanocomposite to separate oils from the water surface. 262 The ability of macropores to remove oil were compared according to their average diameters and the results indicated that larger pores led to a better removal efficiency. In addition, macroporous carbon-based functional magnets can easily collect pollutants from oil and thus, are promising recycling absorbents.…”
Section: Hard-templatesmentioning
confidence: 99%